COVID-19 Pandemic Management in Oil and Gas Company, a Corporate Office Experience Based - Boy Hidayat; Nuri Purwito Adi; Cinthya Yuanita (The Indonesian Journal of Community and Occupational Medicine, 2022)
Background: The COVID-19 pandemic is first and foremost a human tragedy that has played out across the globe. People are experiencing unprecedented levels of disruption in their homes and communities, as well as in their jobs. Office worker of an international oil and gas company located in Jakarta was also had the impact of COVID-19 pandemic. The company must establish system to protect their worker to perform their work safely and avoid COVID-19 exposure.Objective: To describe COVID-19 statistic period 2020 – November 2021 and how company address the system to prevent outbreak and the re-occurrence.Methods: A case study based on company record and performance on tackling COVID-19 problem during 2020 – 2021.Result: Two cases started in March 2020 and total were up to 111 of 800’s workers until Nov 2021. 56% were asymptomatic, 39% were 50 yo or above. 74% did not have co morbid. 46% were domestic cluster. Cases trend were like local and national cases statistic trend.Conclusion: COVID-19 had also impact to corporate office workers which potentially lead to business disruption. The company set dedicated health system to prevent and control COVID-19 system. Principally, it must be set higher than local government standard other than 3M as follows: WFH policy, lowered body temperature identification to min 370C for COVID-19 testing, applied mobile application for health monitoring and tracing, biweekly COVID-19 screening test prior to work at office and included COVID-19 prevention behavior into individual key performance indicator.